9514 1404 393
Answer:
2
Explanation:
A calculator can give you the answer quickly: 2.
__
Working this out in detail is a little more complicated. Eliminating roots in the denominator means multiplying numerator and denominator by the "conjugate" of the denominator.
![(6)/(√(36)+√(27))+(6)/(√(27)+√(18))+(6)/(√(18)+√(9))\\\\=6\left((6-3√(3))/(36-27)+(3(√(3)-√(2)))/(27-18)+(3(√(2)-1))/(18-9)\right)\\\\=(6)/(9)(6-3√(3)+3√(3)-3√(2)+3√(2)-3)=(2)/(3)\cdot 3=\boxed{2}](https://img.qammunity.org/2021/formulas/mathematics/high-school/xoyxjm7v88a2oenz1sg9dz80ts9flfqrxu.png)